eCM 2017
DOI: 10.22203/ecm.v034a08
|View full text |Cite
|
Sign up to set email alerts
|

The effect of whole body vibration on fracture healing – a systematic review

Abstract: This systematic review examines the efficacy and safety of whole body vibration (WBV) on fracture healing. A systematic literature search was conducted with relevant keywords in PubMed and Embase, independently, by two reviewers. Original animal and clinical studies about WBV effects on fracture healing with available full-text and written in English were included. Information was extracted from the included studies for review. In total, 19 articles about pre-clinical studies were selected. Various vibration r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 57 publications
(268 reference statements)
2
42
0
1
Order By: Relevance
“…Taken together, the promotive effect on fracture healing may be dependent on the condition of WBV, and for Power Plate 1 , the amplitude setting may be important. With regard to other devices of WBV, a systematic review on their effects on fracture healing has recently been published and has presented controversial results among in vivo studies [51]. These differences Col-II on days 10 and 14, and ACN on day 14 in the ATDC5 cell line and SOX-9 on day 7, Col-II on days 7 and 10, and ACN on day 14 in the C3H10T1/2 cell line were significantly higher in the V-group than those in the C-group.…”
Section: Plos Onementioning
confidence: 99%
“…Taken together, the promotive effect on fracture healing may be dependent on the condition of WBV, and for Power Plate 1 , the amplitude setting may be important. With regard to other devices of WBV, a systematic review on their effects on fracture healing has recently been published and has presented controversial results among in vivo studies [51]. These differences Col-II on days 10 and 14, and ACN on day 14 in the ATDC5 cell line and SOX-9 on day 7, Col-II on days 7 and 10, and ACN on day 14 in the C3H10T1/2 cell line were significantly higher in the V-group than those in the C-group.…”
Section: Plos Onementioning
confidence: 99%
“…It is noteworthy that mechanostimulation by low-magnitude high frequency vibration was shown to provoke anabolic effects on the intact skeleton of both mice and human. This effect is estrogen-dependent and shown to be mediated primarily via the estrogen receptor alpha in mice, and vibration-induced effects on fracture healing in combination with estrogen treatment have also been shown to improve the osteopenic bone structure and increased the bone stiffness in preclinical studies [14,[39][40][41]. Thus, it is possible that such a combination of treatments rather than estrogen treatment alone could improve the healing of bone fractures by positively affecting callus BMD as measured by pQCT.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, during osteoporotic fracture, there is a lack of evidence on how sarcopenia affects bone healing. Interestingly, our previous studies demonstrated that osteoporotic fractured bone was very sensitive to mechanical signals in the form of vibration, as compared with age‐matched non‐osteoporotic bone, which is contradictory to general belief. Estrogen receptor (ER) is therefore proposed to play a critical role, as ER is also a signaling molecule in mechanotransduction.…”
Section: Discussionmentioning
confidence: 99%